Where heat does not come in waves: a framework for understanding and managing chronic heat - Mayra Cruz; Katharine J Mach; Lynée L Turek-Hankins; Kilan C Ashad-Bishop; Zinzi D Bailey; Scotney D Evans; Ashley Fanning; Margo Fernandez-Burgos; Jane Gilbert; Bereatha Howard; Monique Mahabir; Julia Marturano; et al. (Environmental Research: Climate)
Research on heat and its risks has focused on heat waves as an increasing emergency under climate change, but this emphasis has obscured the chronic—not just acute and episodic—exposure of billions of people globally to increasingly dangerous levels of heat. In many regions, predominantly in the global tropics, heat index exceeds a level of extreme caution according to the US National Weather Service (90°F, 32.2 °C) for more than an entire season and in some cases for much of the year. We propose chronic heat as an alternative framing for heat-related hazards in these regions and demonstrate how its risks differ and are incompletely captured by current heat–health research practices. Chronic heat poses unique risks compared to acute heat because the intersection of enduring societal- and individual-level factors leads to substantially divergent cumulative exposures over seasonal timeframes and associated health outcomes, quality-of-life impacts, and tradeoffs. These multiple interacting factors are difficult to tease out and attribute with traditional heat–health research practices, and therefore understanding of the impacts of chronic heat has remained poor. Further, managing chronic heat requires use of social services, programs, and partners not previously engaged in the context of heat, going beyond heat response as emergency management. Our chronic heat framework identifies a shift needed in heat research and practice to understand and address chronic and cumulative heat exposures increasingly experienced worldwide under intensifying climate change.